Nordic Power System Model Based on Open-Source Data - Model Verification and Power Flow Analyses with Future Generation and Load Scenarios - Arvidsson, Matilda; Klang, Arvid (My University, 2023)
Abstract The Nordic power grid is undergoing a significant transformation in response to ambitious climate goals. Recognizing the urgency of addressing climate change, renewable energy sources are being integrated into the Nordic generation mix rapidly. Furthermore, the electrification of the transport sectors and heavy industry is being prioritized as a key strategy to achieve these goals. To facilitate these changes, the Nordic grid needs to adapt accordingly. In this thesis, a model of the 2020 power system has been developed and verified based on open-source information. Using the information available through the 10- year development plans by the Transmission System Operators (TSOs), this model was also further developed to represent the power system in 2045. In addition, three different load and generation scenarios for 2045, based on projections published by the TSOs, are developed and presented. The compatibility between different generation and load scenarios in high and low wind cases and the planned grid reinforcements are investigated through simulations in PSS/E. Regarding the thermal limitations of the lines in the grid, with the ability to shift loads from low to high generation cases, the grid and the different scenarios were generally compatible after adding some limited reinforcements. However, as this thesis solely concentrates on identifying violations concerning thermal limits within the Nordic power grid in static conditions, further studies are needed to determine whether the established compatibility endures when voltage, frequency, and rotor angle stability in dynamic simulations are considered. With the introduction of large loads at new locations, a shift in power flow was observed. The previously seen north-to-south flow in the Nordics is less prevalent in all 2045 cases. Moreover, with these Gigawatt-sized loads, an increased need for more injected reactive power in proximity to them was observed. Furthermore, suitable locations for new large loads have been investigated and presented.
Keywords: Keywords: Nordic synchronous system, future power system scenarios, renewable power, grid model, open source, PSS/E; Nordic synchronous system; future power system scenarios; renewable power; grid model; open source; PSS/E